Investigation on biodegradability of anaerobic digested sludge - Lim, Eugene Yong Kiat (Nanyang Technological University, 2020)
The biochemical methane potential (BMP) of different sludge, especially anaerobic digested sludge is very important for sludge management. However, this information has barely been explored comprehensively. In this project, 17 types of sludge samples were anaerobically digested to investigate their biodegradability. It was found that the BMP of feed sludge (216.2 – 525.4 mL CH4/g VS) was much greater than anaerobic digested sludge (31.4 – 91.7 mL CH4/g VS), which may be clarified by the higher content of biodegradable compounds in feed sludge compared to digested sludge. In addition, with continuing anaerobic digestion (AD) of digested sludge, the methane generated gradually, suggesting the volatile substrates (VS) of digested sludge could be further reduced. Besides, conventional determination of sludge BMP using anaerobic digesters requires a long period (at least a month). Thus, the possibility of using Near Infrared Spectroscopy (NIRS) to calculate the BMP value of sludge samples with a much-compressed time was evaluated in this study. As a result, a reliable prediction model based on NIRS was established with the coefficient of determination (R2) value of 0.94, residual prediction deviation (RPD) of 4.3 and low root mean square error of cross validation (RMSECV) value of 31.1 mL CH4/g VS. This BMP prediction model is considered to be satisfactory and successfully in application, which could obtain faster and reliable BMP results. Using NIRS for management of sludge would lead to a real benefit from an industrial point of view.